Evidence for a conspecific relationship between two morphologically and cytologically different forms of Korean Anopheles pullus mosquito - Park S.-J. (2014)
Despite the medical importance of anopheline mosquitoes as vectors of Korean vivax malaria, differentiation between Korean anopheline mosquitoes by traditional morphological taxonomic criteria is difficult. An. yatsushiroensis is the second most common Anopheles mosquito species in Korea and a possible vector of Korean vivax malaria together with An. sinensis, the predominant anopheline species. Recently, An. yatsushiroensis has been declared a synonym of An. pullus, based on comparisons of egg morphology and adult progeny, although they differ in ecology and morphology. To verify the species status of these two ambiguous forms, we established isofemale lines of Korean An. pullus and An. yatsushiroensis (An. pullus form yatsushiroensis) mosquitoes and investigated their genetic relationship by metaphase karyotype analysis, comparing the DNA sequences of rDNA internal transcribed spacer 2 (ITS2) and mitochondrial cytochrome c oxidase subunits I (COI) and II (COII), and by hybridization experiments. Two isofemale lines had differently shaped X and Y chromosomes. However reciprocal crosses between them yielded viable progeny with completely synaptic salivary gland polytene chromosomes. DNA analyses also strongly supported their conspecificity. The two strains also showed great sequence similarity in the ITS2, COI and COII regions (variation rate = 0.0 to 0.8%). Based on these findings, we conclude that the two forms, though differing distinctly in morphological, cytological and ecological traits, remain interfertile. ©KSMCB 2003.